Peran Otoritas Jasa Keuangan (OJK) dalam Mengawasi dan Mengatur Implementasi Danantara - Nathanael, Bily Steven; Ridorti, Alnurtia; Fitriadi, Dwinky; Sari, Defita (Universitas Batanghari Jambi, 2025)
The rapid development of financial technology (fintech) has significantly impacted the financial services sector in Indonesia, as evidenced by the Danantara platform. The Financial Services Authority (OJK) plays a crucial role in supervising and regulating fintech implementation to ensure financial system stability and consumer protection. This study employs a literature review method using sources from SINTA-indexed journals from 2014 to 2024 to analyze the OJK's role in supervising Danantara and the implementation of good corporate governance (GCG) principles. The results show that the OJK carries out regulatory functions, such as granting permits, monitoring operations, and imposing sanctions for violations. Through the regulatory sandbox mechanism and ongoing supervision, the OJK strives to create a healthy, transparent, and accountable fintech ecosystem. The study provides a comprehensive understanding of the effectiveness of the OJK's strategy for addressing financial technology disruption and the challenges of maintaining security and public trust in fintech services.